Делопроизводство: Практ. пособие / В. И. Андреева - Андреева В. И. (Интел-Синтез, 1998)
Экземпляры: ЧЗ (20151110) / Инвентарный номер: 33817 / Цена: 19.30 / Сис.шифр: 65.050.9(2)286 / Авт.знак: А65 / ГРНТИ: 06 / ББК: 65.050.9(2)286